Assessing Biology Pre-Service Teachers' Professional Vision of Teaching Scientific Inquiry - Friederike Vogt; Philipp Schmiemann (MDPI AG, 2020)
Professional vision is a key ability in the professional development of pre- and in-service teachers as it determines how professionals perceive and interpret situations. The aim of this study was to conceptualize an instrument for professional vision focusing on formative assessment in the context of scientific inquiry. This focus is highly valuable, since formative assessment contributes to the quality of science teaching and learning. The four-dimensionality of the construct of professional vision with its abilities (perception, description, explanation, and prediction) was confirmed by means of our text-vignette-based instrument. The professional vision of pre-service teachers (N = 80) was fostered in training, involving a seminar phase and a teaching phase in an out-of-school laboratory. In a pre-post design significant interaction effects of groups (training vs. comparison group (N = 39)) and time for the ability description (F(1,117) = 29.14 p < 0.001) and prediction (F(1,117) = 14.81 p < 0.001) were found, indicating the sensitivity of the instrument. Our instrument allows the assessment of the abilities description and prediction. The scales for the abilities perception and explanation need further refinements. Nonetheless, our instrument could be a starting point to further investigate professional vision in science contexts as it incorporates the essential key features such as a situated approach.